A hierarchical simulation methodology for rotary kilns including granular flow and heat transfer. (April 2018) - Witt, Peter J.; Sinnott, Matthew D.; Cleary, Paul W.; Schwarz, M. Philip
Highlights: A new hierarchical approach for modelling rotary kilns combines DEM and CFD. DEM simulations provide constitutive relations for rheology and heat transfer. CFD simulations can then use these to simulate large industrial kilns. A modified Drucker-Prager model is found to be suitable for CFD rheology. Heat transfer in the granular bed is also satisfactorily simulated by the model. Abstract: Rotary kilns are used in several minerals processing operations, as well as related industries such as cement manufacture. Since they involve complex multiphase heat and mass transfer processes, optimization would ideally be guided by numerical modelling. A new generic hierarchical approach is proposed in this paper, sequentially combining 2D Discrete Element Method (DEM) simulations of slices of the bed and 3D two-phase computational fluid dynamics (CFD) models of the entire kiln, encompassing both bed and gaseous freeboard. DEM simulations have been used to derive mean solids velocities in a bed for various rotation speeds and particle sizes, and these were then used to calibrate and validate the solids rheology model used in the subsequent CFD model. A modified Coulombic friction for the bed in the CFD model was shown to give satisfactory agreement with the DEM bed results over a range of rotation speeds. Similarly, thermal mixing simulations carried out using the 2D DEM model for the granular bed were used to validate a CFD model of heat transfer after calibration of the small-scale diffusive term. The capability of the resultant CFD model was demonstrated by 3D simulation of the bed of a large rotary kiln.